KETERWAKILAN PEREMPUAN PADA PEMILU PASCA ORDE BARU - Ekawati, Esty (Musawa Jurnal Studi Gender dan Islam, 2017)
The issue of women’s representation in politics is important because numbers of women who occupy political posi- tions in the party, legislative and executive bodies are still low. In fact, the laws of political parties and elections have provided opportunities for women to be involved in the formal political sphere, especially in the legislature. This is why the role of political parties becomes important in carrying out the function of political recruitment and of course the selection of legislative candidates including women. This article discusses the issues faced by women candidates in the post-New Order Elections that have an impact on the low number of women’s representation in the legislation. By using qualitative method, based on literature study and interview, the study reveals that the low number of women representation in legislative institution is caused by 1) motivation of women to become legislative candidate, 2) patriarchal culture of Indonesian society, 3) limited financial capital, and 4 ) the pragmatism of political parties. This condition is a challenge for women candidates to take political positions in the post-New Order.[Isu keterwakilan perempuan dalam politik ramai diperbincangkan karena masih rendahnya jumlah perempuan yang menduduki jabatan politik baik di internal partai, lembaga legislatif maupun eksekutif. Padahal, undang-undang partai politik dan pemilu sudah memberikan peluang bagi perempuan untuk bisa masuk dalam ranah politik for- mal, khususnya lembaga legislatif. Di sinilah peran partai politik menjadi penting dalam menjalankan fungsi re- kruitmen politik dan tentu saja seleksi calon anggota legislatif termasuk perempuan. Artikel ini membahas per- soalan yang dihadapi oleh kandidat perempuan pada Pemilu pasca-Orde Baru yang berdampak terhadap rendah- nya angka keterwakilan perempuan di legislatif. Dengan menggunakan metode kualitatif berdasarkan studi litera- tur dan wawancara, diketahui bahwa rendahnya angka keterwakilan perempuan di lembaga legislatif disebabkan oleh 1) motivasi kandidat perempuan untuk menjadi caleg, 2) budaya patriarki yang masih melekat di masyarakat Indonesia, 3) keterbatasan modal finansial perempuan, dan 4) pragmatisme partai politik. Kondisi inilah yang men- jadi tantangan bagi kandidat perempuan untuk mengisi jabatan-jabatan politik di Indonesia pasca-Orde Baru.]